INTEGRATION OF DA'WAH VALUES IN KHITOBAH AS STRENGTHENING THE ISLAMIC CHARACTER OF SANTRI PESANTREN ZAINUL HASANAIN GENGGONG PAJARAKAN PROBOLINGGO - Rukmana, Devi; Khumaidi, Ahmad; Solihin, Mohomad (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Speech (Khitobah) is one of the essential activities in pesantren education that not only trains public speaking skills but also serves as a strategic medium for strengthening the values of Islamic preaching (da'wah). Through khitobah, Islamic teachings are not only conveyed but also deeply instilled in the students (santri). This study aims to examine the integration of da'wah values in khitobah activities as a means of strengthening the Islamic character of students at Pesantren Zainul Hasanain Genggong. The method used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. The results of the study indicate that khitobah activities are conducted in a structured manner using the memorization method. The integrated da'wah values include monotheism (tauhid), honesty, justice, Islamic brotherhood (ukhuwah Islamiyah), responsibility, discipline, and cleanliness. These values are integrated through the processes of text preparation, memorization, delivery, and sermon evaluation. The khitobah activity significantly contributes to shaping the Islamic character of students, which is reflected in their behavior and social attitudes in daily life, both within the pesantren environment and in the broader community.